Russia's war on everybody and what it means for you - Giles, Keir 1968- (Bloomsbury Academic, 2022)
" You may not be interested in Russia. But Russia is interested in you. Russia’s 2022 attack on Ukraine saw confrontation between Moscow and the West spill over into open conflict once again. But Russia has also been waging a clandestine war against the West for decades. Hostile acts abroad, from poisoning dissidents to shooting down airliners, interfering in elections, spying, hacking and murdering, have long seemed to be the Kremlin’s daily business. But what is it all for? Why does Russia consistently behave like this? And what does it achieve? In this book, Keir Giles explains how and why Russia pushes for more power and influence wherever it can reach, far beyond Ukraine – and what it means not just for governments, but for ordinary people. Bringing together stories from the military, politics, diplomacy, espionage, cyber power, organised crime and more, Giles describes how Moscow conducts its campaigns across the globe, and how nobody is too unimportant to be caught up in them. By lifting the lid on the daily struggle going on behind the scenes to protect governments, businesses, societies and people from Russian hostile activity, Russia’s War On Everybody shows how Moscow’s hostile intentions for the rest of the world are far broader and more ambitious, and the ways it tries to achieve them far more pervasive and damaging, than we realise."
Angekündigt auch mit dem abweichenden Titel "How Russia gets its way"
Keywords: Geschichte; Information warfare; Außenpolitik; Internationale Politik; Russisch-Ukrainischer Krieg; Geheimunternehmen; Hegemonie; Konfrontation; Krieg; Kriegführung; Russland; Political leadership / Russia (Federation); Russia (Federation) / Politics and government; Western countries / Relations / Russia (Federation); Russia (Federation) / Relations / Western countries; International relations; Political leadership; Politics and government; Russia (Federation); Western countries